Design and Construction of Sandblasting Tools for Metal Surface Cleaner - Situmorang, Riky Stepanus; Prasetya, Muhammad; Haryanto, James; Sabri, M (Talenta Publisher, 2025)
As global technology and industry continue to develop rapidly, the manufacturing industry in Indonesia is also becoming increasingly advanced to keep pace with global industrial progress. A good surface metal is one that is clean from all types of contaminants such as dust, rust, oil, paint, and has a uniform surface roughness. Sandblasting is a method used to remove rust, dirt, and other impurities like oil and paint from metal surfaces. This research aims to design a sandblasting tool using Capstone Design analysis. The process includes selecting the type of sandblasting tool, determining its specifications, and calculating the dimensions of the blasting chamber. Additionally, the study involves assembling the sandblasting chamber, installing the required sandblasting components, as well as testing the functionality of the completed sandblasting system. Based on the functional testing results of the designed sandblasting tool, it can be concluded that the sandblasting tool functioned well and can be used by future researchers. From the roughness test results, it was found that the surface roughness after sandblasting is significantly higher compared to the initial condition.